Follow up study to assess the use and performance of household water filters in Zambia - Rachel Peletz; Michelo Simuyandi; M. Simunyama; K. Sarenje; P. Kelly; T. Clasen (2013)
Effective household water treatment has the potential to improve drinking water quality and prevent diarrhoeal disease if used correctly and consistently over time. We previously conducted a randomized, controlled trial of water filters among households in Zambia with children under two years of HIV-positive mothers. One year after completion of the trial, we conducted a follow up study to assess use and performance the household filters. Ninety percent of participating households met the criteria for current users, and 75% had stored water with lower levels of faecal contamination than source water. Although this study provides some encouraging evidence about the potential to maintain HWTS use and performance, further research is necessary to assess whether these results can be achieved over longer periods and with larger populations.